Impact of the COVID-19 on Cancer Management at Birat Medical College and Teaching Hospital, Nepal - Sapkota, Sulav; Priyadarshini, Mona (Asian Journal of Medical Sciences, 2021)
Background: Coronavirus disease which has become a pandemic has also impacted cancer service to a small country like Nepal which has very low resources. Aims and Objectives: Covid infection itself and the lockdown implemented by the government resulted negative impact in our cancer management. Hence the aim of the study was to delineate the impact of Covid in cancer management. Materials and Methods: We did a prospective descriptive study from 1st March 2020 till 1st August 2020 in our medical oncology department at Birat Medical College and Teaching Hospital (BMCTH). Results: We had 60% reduction in the newly diagnosed cases, 40% decrement in the chemotherapy admissions and total fourteen mortalities. PCR test was advised for all the COVID suspects with features of fever and separate observation ward was started for such patients. Delayed in the cancer diagnosis and treatment could result in increase in the advanced cancer burden which can overwhelm the health service in Nepal. Conclusion: COVID 19 had negative impact on cancer treatment and management at our institution.